Seismic Fragility Curves for Performance of Semi-rigid Connections of Steel Frames - Mohamed Saadi; Djarir Yahiaoui; Noureddine Lahbari; Bouzid Tayeb (Civil Engineering Journal, 2021)
A steel frame with a semi-rigid connection is one of the most widely used structural systems in modern construction. These systems are cheap to make, require less time to construct and offer the highest quality and reliable construction quality without the need for highly skilled workers. However, these systems show greater natural periods compared to their perfectly rigid frame counterparts. This causes the building to attract low loads during earthquakes. In this research study, the seismic performance of steel frames with semi-rigid joints is evaluated. Three connections with capacities of 50, 70 and 100% of the beam’s plastic moment are studied and examined. The seismic performance of these frames is determined by a non-linear static pushover analysis and an incremental dynamic analysis leading finally to the fragility curves which are developed. The results show that a decrease in the connection capacity increases the probability of reaching or exceeding a particular damage limit state in the frames is found. Doi: 10.28991/cej-2021-03091714 Full Text: PDF